A combinatorial αβ T cell receptor expressed by macrophages in the tumor microenvironment - Fuchs, Tina; Riabov, Vladimir; Yin, Shuiping; Kzhyshkowska, Julia; Busch, Svenja; Neumaier, Michael; Kaminski, Wolfgang E. (Immunobiology, 2017)
Recent evidence indicates the presence of macrophage subpopulations that express the TCRαβ in two major inflammatory diseases, tuberculosis and atherosclerosis. Inflammation is also a well-established attribute of cancer progression and macrophages are one of the major immune cells that infiltrate tumors. Here, we demonstrate that the macrophage-TCRαβ is expressed in the tumor microenvironment of human and murine malignancies. We identify TCRαβ+ macrophages in each case of four randomly selected distinct human tumor entities. In human tumor tissues, the TCRαβ expressed by macrophages in the tumor microenvironment is a combinatorial and individual-specific immune receptor. Furthermore, we routinely find TCRαβ+ macrophage subpopulations in experimental tumors (TS/A, mammary adenocarcinoma) which we induced both in normal mice and mice deficient in the macrophage receptor stabilin-1. Expression of the combinatorial murine tumor macrophage TCRαβ is individual-specific and independent of stabilin-1. These results demonstrate that TCRαβ expression is a characteristic feature of macrophages in the tumor microenvironment and identify an as yet unrecognized flexible element in the macrophage-based host response to tumors.